Electrically Programmable Interfacial Adhesion for Ultrastrong Hydrogel Bonding. Issue 13 (21st February 2022) - Liu, Yaqian; Wang, Pudi; Su, Xing; Xu, Liang; Tian, Zhuoling; Wang, Hao; Ji, Guojun; Huang, Jianyong
Abstract: Adjustable interfacial adhesion is of great significance in smart‐hydrogel‐related engineering fields. This study presents an electroadhesion strategy for universal and ultrastrong hydrogel bonding with electrically programmable strength. An ionic hydrogel containing lithium ions is designed to achieve hydrated‐ion‐diffusion‐mediated interfacial adhesion, where external electric fields are employed to precisely control spatiotemporal dynamics of the ion diffusion across ionic adhesion region (IAR). The hydrogel can realize a universal, ultrastrong, efficient, tough, reversible, and environmentally tolerant electroadhesion to diverse hydrogels, whose peak adhesion strength and interfacial adhesion toughness are as high as 1.2 MPa and 3750 J m −2, respectively. With a mechanoelectric coupling model, the dominant role of the hydrated ions in IAR played in the interfacial electroadhesion is further quantitatively revealed. The proposed strategy opens a door for developing high‐performance adhesion hydrogels with electrically programmable functions, which are indispensable for various emerging fields like flexible electronics and soft robotics. Abstract : An electroadhesion strategy capable of realizing ultrastrong and universal hydrogel bonding in an electrically programmable way is reported. With the synergistic effect of electric fields and entropy on hydrated ion diffusion, its peak adhesive strength can reach 1.2 MPa. Further, a mechanoelectric coupling model is established to determine directional diffusion of the ions and resultant smart electroadhesion.